Evolution of change management models and their future in the context of ONA - Szarek, Anna (Management Sciences, 2017)
The aim of the article is to present evolution in change management models and the need of redesigning the current change management concepts with the use of organisational network analysis. Firstly, the article summarizes the evolution of change management approaches presenting the theoretical background of the need to revise change management models. Then the author underlines benefits of organisational network analysis enabling deep research on current change management trends. In addition, the article uncovers very introductory empirical research aimed at estimating the need for revitalising change management models. Finally, the author proposes further empirical research linking change management models and organisational network analysis
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 1 (30), s. 16-23
Keywords: analiza sieci społecznych; analiza sieci organizacyjnych; organisational network analysis; change management; organisational changes; project management; zarządzanie zmianą; zmiany organizacyjne